2019
DOI: 10.2139/ssrn.3427252
|View full text |Cite
|
Sign up to set email alerts
|

Digital Skill Sets for Diverse Users: A Comparison Framework for Curriculum and Competencies

Abstract: (Seattle IT) delivers powerful information solutions for the City and the public we serve. As Seattle strives to become a safe, affordable, vibrant, innovative and connected City, the need for effective technology solutions is critical. Seattle IT supports City departments in the pursuit of this mission by connecting people with their government, ensuring an effective and productive workforce, and building a digitally equitable community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Perhaps it also suggests the pervasiveness of deficit discourses surrounding refugee learners (Ryu & Tuvilla, 2018;Shapiro & MacDonald, 2017). Teaching critical digital literacies also seemed to be particularly challenging when working with beginner level learners which echoes previous research (Waring & Evans, 2015). The framework and guide directed teachers' attention to the importance of critical literacies but there did not seem to be a developed praxis and situated understanding in the case of most of the teachers.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Perhaps it also suggests the pervasiveness of deficit discourses surrounding refugee learners (Ryu & Tuvilla, 2018;Shapiro & MacDonald, 2017). Teaching critical digital literacies also seemed to be particularly challenging when working with beginner level learners which echoes previous research (Waring & Evans, 2015). The framework and guide directed teachers' attention to the importance of critical literacies but there did not seem to be a developed praxis and situated understanding in the case of most of the teachers.…”
Section: Discussionsupporting
confidence: 51%
“…They usually outline various prescribed dimensions of digital competencies that are required for particular contexts and different age groups. Some of them are increasingly used in different learning contexts and are accompanied by free repositories of resources (e.g., Seattle Digital Equity Initiative Skills Framework (Wedlake & Keyes, 2019) and The Digital Skills Library (https://digitalskillslibrary.org/)). Our critical analysis, however, suggested that these frameworks were unsuitable for the AMEP context.…”
Section: Critical Literature Review: Framework and Modelsmentioning
confidence: 99%
“…Another approach emphasizes how ICTs can facilitate digital citizenship by increasing participation and knowledge of city services, such as education, health, and public transport. Other frameworks prioritize 21st century digital skills that allow citizens to leverage ICTs through skills like critical thinking, problem-solving, communication, collaboration, and safety (Economou, 2016;Ferrari, 2012;Iordache, et al, 2017;Law, et al, 2018;Wedlake et al, 2019).…”
Section: Review Of Digital Skills Frameworkmentioning
confidence: 99%
“…These frameworks and indexes classify DS to usage levels as academic studies. For example, Wedlake et al (2019) categorize the DS as communication, creation, gateway, information, online living, privacy and security skills with device ownership, and lifelong learning. According to Motyl et al (2017), DS consists of all technology-linked skills, from main skills for all employees to special skills for ICT professionals.…”
Section: Conceptual Framework 21 Digital Skillsmentioning
confidence: 99%